Evidence for an Adaptation of a Phage-Derived Holin/Endolysin System to Toxin Transport in Clostridioides difficile - Mehner-Breitfeld, Denise; Rathmann, Claudia; Riedel, Thomas; Just, Ingo; Gerhard, Ralf; Overmann, Jörg; Brüser, Thomas (Frontiers in Microbiology, 2018)
The pathogenicity locus (PaLoc) of Clostridioides difficile usually comprises five genes (tcdR, tcdB, tcdE, tcdA, tcdC). While the proteins TcdA and TcdB represent the main toxins of this pathogen, TcdR and TcdC are involved in the regulation of their production. TcdE is a holin family protein, members of which are usually involved in the transport of cell wall-degrading enzymes (endolysins) for phage-induced lysis. In the past, TcdE has been shown to contribute to the release of TcdA and TcdB, but it is unclear whether it mediates a specific transport or rather a lysis of cells. TcdE of C. difficile strains analyzed so far can be produced in three isoforms that are initiated from distinct N-terminal ATG codons. When produced in Escherichia coli, we found that the longest TcdE isoform had a moderate effect on cell growth, whereas the shortest isoform strongly induced lysis. The effect of the longest isoform was inhibitory for cell lysis, implying a regulatory function of the N-terminal 24 residues. We analyzed the PaLoc sequence of 44 C. difficile isolates and found that four of these apparently encode only the short TcdE isoforms, and the most closely related holins from C. difficile phages only possess one of these initiation codons, indicating that an N-terminal extension of TcdE evolved in C. difficile. All PaLoc sequences comprised also a conserved gene encoding a short fragment of an endolysin remnant of a phage holin/endolysin pair. We could produce this peptide, which we named TcdL, and demonstrated by bacterial two-hybrid analysis a self-interaction and an interaction with TcdB that might serve to mediate TcdE-dependent transport.